Middle-range theory of the diagnosis of low situational self-esteem in undergraduate nursing students - Laís Vasconcelos Santos; Layane Ryane da Silva Souza; Marcos Manoel Sousa Silva; Marcos Venícios de Oliveira Lopes; Ana Luisa Brandão de Carvalho Lira (Revista Latino-Americana de Enfermagem)
Objective: to elaborate a Middle-Range Theory for the diagnosis of situational low self-esteem in nursing students based on the mapping of scientific literature. Method: methodological study aimed at building a Middle-Range Theory, developed on the basis of the causal-theoretical model and based on Roy’s Adaptation Model. The process was operationalized in six stages: (1) defining the approach to building the theory; (2) defining the theoretical-conceptual models; (3) identifying the key concepts; (4) drawing up a pictorial scheme; (5) formulating propositions; and (6) establishing causal relationships and evidence for practice. Results: five essential attributes, 15 antecedents and 23 clinical consequents were identified. The analysis of these elements enabled the development of the Middle-Range Theory, consisting of an illustrative diagram, eight propositions, 12 causal relationships and evidence for practice. Conclusion: the small number of studies shows how little the subject has been explored in national and international contexts. The Middle-Range Theory broadened the understanding of the diagnosis of situational low self-esteem, offering support for nurses’ work in the university context.